2020
DOI: 10.3747/co.27.6643
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 on Canadian Medical Oncologists and Cancer Care: Canadian Association of Medical Oncologists Survey Report

Abstract: Background  The covid-19 pandemic has presented unprecedented professional and personal challenges for the oncology community. Under the auspices of the Canadian Association of Medical Oncologists, we conducted an online national survey to better understand the impact of the pandemic on the medical oncology community in Canada. Methods  An English-language multiple-choice survey, including questions about demographics, covid-19 risk, use of personal protective equipment (ppe), personal challenges,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
49
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(55 citation statements)
references
References 4 publications
4
49
0
1
Order By: Relevance
“…Regarding everolimus and sunitinib, to date there is no available scientific data to compare this figure with other reports even outside the setting of NEN patients. As far as chemotherapy is concerned, other surveys performed of nonendocrine cancers have reported a low proportion of oncologists who changed treatment plans in their clinical practice [19,20]. This figure is in agreement with data reported by the present survey, confirming the ability of the NEN dedicated teams to continue to provide optimal care to their patients.…”
Section: Discussionsupporting
confidence: 92%
“…Regarding everolimus and sunitinib, to date there is no available scientific data to compare this figure with other reports even outside the setting of NEN patients. As far as chemotherapy is concerned, other surveys performed of nonendocrine cancers have reported a low proportion of oncologists who changed treatment plans in their clinical practice [19,20]. This figure is in agreement with data reported by the present survey, confirming the ability of the NEN dedicated teams to continue to provide optimal care to their patients.…”
Section: Discussionsupporting
confidence: 92%
“…In assessing care patterns and patient perspectives, we found that nearly two-thirds of study participants reported having a virtual oncology appointment during the first wave of the COVID-19 pandemic. This corroborates findings of a recent survey of Canadian medical oncologists that reported 82% used some form of virtual care [ 6 ]. Furthermore, our finding that the majority of patients (83%) were satisfied with their virtual oncology appointments provides reassurance to healthcare providers.…”
Section: Discussionsupporting
confidence: 91%
“…The most common psychological symptoms measured with surveys or validated questionnaires reported included anxiety ( n = 103), depression ( n = 73), stress ( n = 68), fear ( n = 61), burnout ( n = 25), mental distress/health ( n = 21), and post-traumatic stress disorder (PTSD) ( n = 14) (Additional File 3 ). Most COVID-19 studies reported on physicians from USA ( n = 23) [ 41 , 52 , 66 , 70 , 77 , 90 – 107 ], China ( n = 22) [ 15 , 49 , 54 56 , 65 , 68 , 73 , 86 , 89 , 102 , 108 118 ] followed by India ( n = 21) [ 40 , 50 , 58 , 63 , 67 , 71 , 102 , 119 – 132 ] [ 41 , 52 , 66 , 70 , 77 ], Italy ( n = 10) [ 32 , 94 , 102 , 125 , 133 138 ], and Turkey ( n = 11) [ 35 , 44 , 94 , 139 – 146 ] [ 28 , 30 , 32 , 34 , 36 , 37 , 42 , 45 , 47 , 48 , 59 , 60 , 62 , 80 , 87 ]. .Sixtee...…”
Section: Resultsmentioning
confidence: 99%